Harald Szeemann museum of obsessions - Phillips, Glenn 1974-; Kaiser, Philipp 1972-; Chon, Doris; Rigolo, Pietro 1981- (Getty Research Institute, 2018)
"An examination of the career of the influential Swiss curator Harald Szeemann (1933-2005), drawing on his extensive archive and library housed at the Getty Research Institute, Los Angeles"...Provided by publisher
"This publication accompanies the exhibition Harald Szeemann: Museum of Obsessions, on view at the Getty Research Institute at the Getty Center, Los Angeles, from February 6 to May 6, 2018."...ECIP galley. - Includes index
Keywords: Szeemann, Harald -- Criticism and interpretation; Szeemann, Harald -- Exhibitions; Szeemann, Harald -- 1933-2005; Art museum curators -- Switzerland -- Exhibitions; Art critics -- Switzerland -- Exhibitions; Art -- Exhibition techniques; Art -- Exhibitions -- Philosophy; Ausstellungskatalog -- Getty Center -- 06.02.2018-06.05.2018 -- Los Angeles; Ausstellungskatalog -- Kunsthalle Bern -- 09.06.2018-02.09.2018 -- Bern; Ausstellungskatalog -- Kunsthalle Düsseldorf -- 10.10.2018-20.01.2019 -- Düsseldorf; Ausstellungskatalog -- Castello di Rivoli, Museo d'Arte Contemporanea -- 26.02.2019-26.03.2019 -- Turin